Dietary modifications for hospitalized patients with relevant comorbidities: The need of the hour - Khurram Rehman , Nadir; Khalid, Fizza (Journal of the Pakistan Medical Association, 2026)
Dear Editor, During the last few years, the ERAS (Enhanced Recovery After Surgery) protocol has been considered a major step towards early patients’ recovery, decreased hospital stay, postoperative complications, and mortality. Perioperative nutrition is the main element of the ERAS protocol.1 However, optimal nutritional support is equally critical for all hospitalised patients, whether under medical or surgical care. As Alyssa R Cass et al say, malnutrition is acquired during hospitalisations, leading to delayed wound healing, increased infection rate, and worsening of ailments. The documented contributing factors towards malnutrition include decreased oral intake, inappropriate meals, and the effect of illness. 2 Increased glucose variability has also been associated with increased morbidity and mortality among critically ill patients admitted to the ICU.3 A significant concern in many settings, including state-funded hospitals, is that the general food provided to inpatients is not individualised according to specific dietary requirements and restrictions. Meals that are low in protein but high in fat, sodium, and refined carbohydrates are routinely served to all patients, including those with diabetes, hypertension, and cardiac, renal, or hepatic pathologies. This institutional dietary inadequacy constitutes a form of malnutrition that impedes recovery. It also creates a financial burden when patients or their families are compelled to seek appropriate food externally. For instance, we have observed cases where patients with diabetes and cholelithiasis were provided with high-glycaemic and high-fat meals, potentially exacerbating hyperglycaemia and biliary symptoms. It is important to focus on food optimisation according to the patient’s health status. Hypertensive patients should be given vegetables, fruits, yogurt, whole grains, cereals and the food cooked in vegetable oil with low trans-fat content which helps in not only decreasing blood pressure, but also lessens cardiovascular problems and insulin resistance.4And diabetic patients are benefited by high protein diet including fish, eggs, meat , as high protein diet has been documented to decrease glucose variability and insulin resistance.5 It is important to clarify that this refers to a controlled, isocaloric high-protein dietary intervention, not an unrestricted increase in protein intake, particularly for patients with renal impairment. While implementing such tailored nutritional services requires dedicated resources and systematic assessment of patient comorbidities, the long-term benefits are substantial. Standardised therapeutic diets would facilitate faster recovery, shorten hospital length of stay, reduce complication rates, and ultimately lessen the financial strain on healthcare systems.